2767. Variation in Incidence of Pediatric Herpes Zoster by First- and Second-Dose Varicella Vaccine Formulations - Weinmann, Sheila (Open Forum Infect Dis, 2019)
BACKGROUND: Varicella (VAR) and measles-mumps-rubella (MMR) vaccines are recommended for children at ages 12–15 months and 4–6 years. These are administered as separate MMR and VAR vaccines (MMR+VAR) or as combined measles-mumps-rubella-varicella (MMRV) vaccine. Herpes zoster (HZ), caused by wild-type or vaccine-strain varicella-zoster virus, can occur in children after varicella vaccination. It is unknown whether HZ incidence after varicella vaccination varies by vaccine formulation or simultaneous receipt of MMR. METHODS: Using data from six integrated health systems, we examined HZ incidence among children who turned 12 months old during 2003–2008 and received varicella and MMR vaccines according to routine recommendations. All HZ cases ≥ 21 days after first varicella vaccination were identified using ICD-9 codes from inpatient, outpatient, emergency room encounters, and claims data, through 2014. HZ incidence was examined by vaccine formulation (MMR+VAR, MMRV, or VAR without same-day MMR) and doses received and compared using incidence rate ratios (IRR). RESULTS: Among 199,797 children, we identified 601 HZ cases. Crude HZ incidence after first-dose MMR+VAR (18.6 [95% CI 11.1–29.2] cases/100,000 person-years) was similar to the rate after first-dose MMRV (17.9 [95% CI 10.6–28.3] cases/100,000 person-years), but approximately double the rate among those with first-dose VAR without same-day MMR (7.5 [95% CI 3.1–15.0] cases/100,000 person-years); see Table 1. The IRR for HZ after first-dose MMR+VAR or MMRV, compared with VAR, was 2.5 (95% CI 1.4–4.4; P = 0.002). When examining any first or second dose formulation, crude HZ incidence was lower after the second varicella vaccine dose (13.9 cases/100,000 person-years), than in the period before the second dose (i.e., between first and second doses or after the first dose in children with only one dose; 21.8 cases/100,000 person-years, P < 0.0001). HZ incidence was also lower after two varicella vaccine doses in each of the three first-dose formulation groups. CONCLUSION: HZ incidence among children varied by first-dose varicella vaccine formulation and number of varicella vaccine doses. Regardless of the first-dose varicella vaccine formulation, children who received two vaccine doses had lower HZ incidence after the second dose. [Image: see text] DISCLOSURES: All authors: No reported disclosures.